A real-time PCR method to assess the presence of vertebrate material in plant-based products. (July 2021) - Cottenet, Geoffrey; Blancpain, Carine
Abstract: Consumption of plant-based products and meat alternatives has been rising for a few years, with vegetarian and vegan diets gaining more and more popularity. To comply with legislation and maintain consumers' trust, food manufacturers of vegan products must ensure the absence of animal residues in these products. A real-time PCR method targeting the 16S mitochondrial rRNA gene from vertebrates has been developed in order to detect the presence of vertebrate material in plant-based ingredients and finished products. The reaction successfully amplified on mammals, birds, reptiles and fish samples only. The analysis of plant-based samples spiked at 0.1% (w/w) with meat or fish materials confirmed the sensitivity of the method at this level, considered as the limit for unintended presence of animal residues by the European Vegetarian Union. The method was applied to commercialized vegan finished products from European markets and confirmed the absence of animal material in all the tested samples. Highlights: New real-time PCR method to detect vertebrates in plant-based products. Limit of detection determined at 0.1% (w/w) aligned with the European V-label. Method applicable on plant-based ingredients and vegan finished products. 24 commercialized European vegan products tested, none contained animal material.